2011
DOI: 10.1155/2011/705345
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Epithelioid Malignant Peripheral Nerve Sheath Tumor Showing Complete Response to Combined Surgery and Chemotherapy: A Case Report

Abstract: Malignant peripheral nerve sheath tumor (MPNST) is a rare high-grade soft tissue sarcoma. The epithelioid variant accounts for 5% or less of MPNSTs; the clinical behavior of this variant is unclear. Reports of approximately 40 cases are available in the English literature; however, most reports addressed clinicopathological features rather than therapeutic procedures or clinical courses. We describe a case of a 62-year-old male with an epithelioid MPNST of the left foot. Multiple lung metastases developed aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Several case reports have demonstrated the efficacy of neoadjuvant chemotherapy followed by surgery for advanced MPNST . However, no information is available regarding the efficacy of neoadjuvant chemotherapy for advanced intrathoracic MPNST.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several case reports have demonstrated the efficacy of neoadjuvant chemotherapy followed by surgery for advanced MPNST . However, no information is available regarding the efficacy of neoadjuvant chemotherapy for advanced intrathoracic MPNST.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have demonstrated the efficacy of neoadjuvant chemotherapy followed by surgery for advanced MPNST. [10][11][12] However, no information is available regarding the efficacy of neoadjuvant chemotherapy for advanced intrathoracic MPNST. The resectability of the remaining tumor after chemotherapy may be an important issue in patients with locally advanced intrathoracic MPNST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Doxorubicin is one of the anthracycline drugs used widely for treatment of several malignant solid and soft tissue cancers. Few case studies were reported where doxorubicin alone or in combination with other chemotherapeutic agents were used to treat MPNSTs with moderate efficacy[ 41 – 43 ]. Doxil, a pegylated liposomal doxorubicin, was demonstrated previously to be effective in metastatic soft tissue sarcoma patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%